قدرة بعض العزلات الفطرية المحلية على إنتاج أنزيم الليباز وتحديد الظروف المثلى لإنتاجه من Penicilliumdevirsum - سارة سناء (Latakia University Journal -Biological Sciences Series, 2017)
تمّ الكشف عن قابلية العزلات الفطريــــــة المحليــــة الآتية:Aspergillus niger،Alternariaalternata، Fusariumoxysporum، Fusarium solani وPenicilliumdevirsum،على إنتاج أنزيم الليباز باستخدام الوسط الصلب المحتوي على مادة Triputyrin. تميّز الفطر P.devirsum بنشاطه الأنزيمي على بقية الفطور، بينما فشل الفطر A.alternata في إنتاج الليباز. ثمّ أجريّ اختبار كمي باستخدام الوسط السائل لتحديد الظروف المثلى (المصدر الكربوني وتركيزه، فترة الحضن، درجة الحرارة، pH الوسط، المصدر النيتروجيني)لأفضل نمو للفطر P. devirsum ولأفضل إنتاج لأنزيم الليباز. فتبين أنّ زيت الذرة هو الأفضل كمصدر كربوني لنمو الفطر بعد 5 أيام من الحضن، إذ بلغت الكتلة الحيوية(15.99 g/L)وبلغت فعالية الليباز(67.43%) . وقد حقق زيت الذرة بتركيز 2% أفضل كتلة حيوية(17.83g/L) وأفضل فعالية لأنزيم الليباز(72.78%). وحققت درجة الحرارة 34C أعلى كتلة حيوية (18.94 g/L) وأفضل فعالية للأنزيم(76.16%)، وكانت pH=7.0هي المثلى لنمو الفطر بكتلة حيوية (21.87 g/L)وبفعالية أنزيمية (82.93%). في حين أعطى المصدر النتروجيني ببتون أكبر قيمة للكتلة الحيوية (27.08 g/L) وأقصى فعالية للأنزيم(88.12%)، وذلك في الشروط المثلى التي تمّ التوصّل إليها في هذه الدراسة. It wasdetected for the ability of a local fungus A.niger, A.alternata, F.oxysporum, F.solaniandP.devirsum to produce the enzyme lipase in solidmedium including Triputyrin. The enzymic activity of P.devirsum fungus is distinction from other fungus, while the fungus A.alternata failed to produce the lipase. Then they tested quantitatively using a liquid center to determine the best conditions for best growth to fungus P.devirsum and for best produce to enzyme lipase. It indicates that corn oil is the best carbonic source for growth of fungus after 5 days of incubation, as biomass reached(15.99g/L) and effective of lipase (67.43%).And it found that the concentration of 2% of the corn oil has achieved best biomass (17.83g/L) and best production of enzyme lipase effectively(72.78%). Temperature 34 c achieved the highest biomass (18.94g/L) and best production of enzyme lipase (76.16%), and pH =7 was the best for the growth of fungus in biomass reached (21.87g/L) and production of lipase effectively (82.93%). While the nitrogenic source gave peptone biggest value to biomass (27.08 g/L) and highest production for enzyme (88.12%) in optimal conditions reached.